Sequential alteration in some of the haemato-biochemical indices during post foaling period in Kathiawari mares - MADAN, ARUN KUMAR; KUMAR, JITENDER; SINGH, YASHWANT (The Indian Journal of Animal Sciences, 2014)
Haematological and blood biochemical indices of 4 Kathiawari postpartum mares were evaluated for 8 weeks. During the post foaling period, initially haemoglobin, packed cell volume and total erythrocyte count decreased while total leukocyte count increased and regained the normal values by eighth week. Blood glucose, protein, cholesterol, urea, chloride and creatinine concentrations decreased during the initial 1 to 2 weeks but reached to almost normal values by eighth week. However, serum sodium and potassium profile did not change much during expenment. Our results give an insight of the haemato-biochemical alterations in mares immediately after foaling, and also in the management of emergency cases.